Ketidakadilan dan Kepercayaan dalam Naskah Drama Matahari di Sebuah Jalan Kecil Karya Arifin C. Noor : (Pendekatan Semiotika Roland Barthes) - Erni Febriyani; Ana Aulia; Agung Yudistira; Anggun Widhiyani; Nabil Tsaqif; Davila Anggara; Kintan Audina; Azi Najar; Tyara Widhianingsih; Widati Widati; Ilmi Solihat (FKIP, Universitas Palangka Raya, 2026)
This study aims to uncover the hidden sign system and meanings in the drama script Matahari di Sebuah Jalan Kecil by Arifin C. Noor using Roland Barthes’ semiotic approach. The drama depicts the social conditions of lower-class communities facing economic pressure, moral conflict, social inequality, and the erosion of interpersonal trust in everyday life (Azizah et al., 2025). This research employs a descriptive qualitative method with semiotic analysis consisting of three main levels: denotation, connotation, and myth. The findings indicate that important signs in the drama, such as the symbol “Sun” and the characters “Pemuda” and “Simbok,” represent profound social criticism of poverty, corruption, injustice, and the decline of empathy within society. Through Barthes’ semiotics, Pemuda’s inability to pay for food is not merely interpreted as an economic incident but as a sign of social despair. This condition is further reinforced by the myth that poor people are inherently associated with dishonesty. Overall, the drama reflects a complex social reality rich in humanistic critique.